2013
DOI: 10.1097/hjh.0b013e32835ac7b5
|View full text |Cite
|
Sign up to set email alerts
|

Association between urinary albumin excretion and both central and peripheral blood pressure in subjects with insulin resistance

Abstract: Although cBP is related with UAE, this relationship is not superior to that of office peripheral BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Interestingly it was noted that the association was non-linear, suggesting a threshold above which the hemodynamic effects of elevated PP exerts a renal effect. Similar findings have been shown in other studies [40,41]. It has been suggested that elevated PP may result in excessive penetration of pulsatile energy to the kidney, ultimately damaging the renal microvasculature and leading to wall hypertrophy, as seen in renal biopsies of mildly proteinuric hypertensive patients [42].…”
Section: Nephropathysupporting
confidence: 64%
“…Interestingly it was noted that the association was non-linear, suggesting a threshold above which the hemodynamic effects of elevated PP exerts a renal effect. Similar findings have been shown in other studies [40,41]. It has been suggested that elevated PP may result in excessive penetration of pulsatile energy to the kidney, ultimately damaging the renal microvasculature and leading to wall hypertrophy, as seen in renal biopsies of mildly proteinuric hypertensive patients [42].…”
Section: Nephropathysupporting
confidence: 64%
“…Goupil et al also found that microalbuminuria and early chronic kidney disease were not associated with office central BP [5]. A previous study from our group showed similar correlation of microalbuminuria with office central BP and office brachial BP [18]. Finally, in a Chinese community, Fan et al found that, compared with office brachial SBP, office central SBP was a stronger predictor for kidney function decline [6].…”
Section: Discussionmentioning
confidence: 88%
“…Their development is based on the premise that central or aortic BP reflects the true load on the target organ. In fact, several studies have suggested that central BP is associated with the macrovascular damage, specifically cardiac and carotid damage, but is not so closely related to the microvascular lesion [2, 4, 6, 15-18]. Kollias et al analyzed four studies that showed similar correlations of urine albumin excretion with brachial SBP and central BP (three in an office setting and one with ABPM) [2].…”
Section: Discussionmentioning
confidence: 99%
“…The pooled correlations between cPP and pPP with cfPWV ( r = 0.41 and 0.35 for cPP and pPP, respectively) were similar to the findings of the present study ( r = 0.41 and 0.40 for cPP and pPP, respectively), but the correlation coefficients were higher for ACR and lower for carotid IMT in the present study. Some studies show that urinary albumin excretion assessed by 24-h urine protein or ACR [3,15] have similar correlation with central and peripheral pressure. In our study, we found that cPP was more closely correlated with urinary albumin excretion assessed by ACR than pPP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in blood pressure measurement have enabled the combination of the conventional brachial sphygmomanometer with a peripheral pulse waveform to estimate central aortic pressure (AP) non-invasively [2]. A number of studies have shown that central aortic blood pressure could better reflect the load on the heart and central vasculature and organs [3,4]. Central aortic pulse pressure (PP) showed higher correlation with carotid atherosclerosis and the incidence of cardiovascular events than peripheral PP [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%